2012
DOI: 10.1108/00251741211266732
|View full text |Cite
|
Sign up to set email alerts
|

Impact of knowledge brokering on performance heterogeneity among business models

Abstract: Purpose

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
0
23
0
4
Order By: Relevance
“…Sujith et al (2012) argue that firms' performance differences could accrue from knowledge brokering capability of TMT. Knowledge brokering has been defined as systematic approaches to seek extended ideas from people in a variety of industries, disciplines, and contexts and then combining the resulting lesson in a new way (Davidson & Billington, 2010).…”
Section: Effects Of Generic Strategies On Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Sujith et al (2012) argue that firms' performance differences could accrue from knowledge brokering capability of TMT. Knowledge brokering has been defined as systematic approaches to seek extended ideas from people in a variety of industries, disciplines, and contexts and then combining the resulting lesson in a new way (Davidson & Billington, 2010).…”
Section: Effects Of Generic Strategies On Firm Performancementioning
confidence: 99%
“…Furthermore, Bharadwaj et al (1993) cited in Sujith et al (2012) suggest that the firm performance differences could be explained by the development of particular resources and capabilities that the firm possesses that are not available in the competitors. Likewise, Thomas and William (2004) suggested that the ability to impact a cost leadership, differentiation, or focus strategies is dependent on firm's ability to develop specific set of competitive methods.…”
Section: Effects Of Generic Strategies On Firm Performancementioning
confidence: 99%
“…In their definition of business models, Chesbrough and Rosenbloom (2002) emphasize the connections that a business model provides between a firm's potential and the realization of economic value. Business models have a profound influence on firm performance heterogeneity among intra-industry firms (Afuah & Tucci, 2001;Nair et al, 2012;Zott & Amit, 2008) as they 'try to find new ways of doing business that will disrupt an industry's existing competitive rules, leading to the development of new business models' (Ireland, The Service Industries Journal Hitt, Camp, & Sexton, 2001). Business model innovation affects the entire organization (Amit & Zott, 2001) unlike normal business changes, which are intended to improve the strategic or operational efficiency of the firm.…”
Section: Business Model Innovation and Firm Competenciesmentioning
confidence: 98%
“…Initially developed in the field of manufacturing and dubbed agility (D'Aveni & Gunther, 1994;Yusuf, Sarhadi, & Gunasekaran, 1999), the concept of flexibility (Carlsson, 1989) has recently attracted the attention of service management scholars as well (Aranda, 2003;Arias-Aranda, Bustinza, & Barrales-Molina, 2011;Karmarkar, 2004;Menor & Mason, 2001). Service firms need to adapt rapidly to changing global environments, innovating their business models to react to new challenges and market opportunities (Nair, Nisar, Palacios, & Ruiz, 2012;Wright, Snell, & Dyer, 2005). While the importance of flexibility (Anand & Ward, 2004;Narasimhan, Swink, & Kim, 2006) and its role in business model innovation (Johnson, Christensen, & Kagermann, 2008;Zott, Amit, & Massa, 2011) is widely recognized in the literature, the core competence strategies required for the dynamic capability of flexibility to enable business model innovation have not gained much attention.…”
Section: Introductionmentioning
confidence: 98%
“…Hargadon, 2002;Hargadon and Sutton, 2000;Nair et al, 2012 Knowledge brokering refers to the process of bridging disconnected ideas from at least two distant organizations. Simultaneously it involves some form of transformation of these ideas, into the new context (Bergenholtz, 2011).…”
Section: Knowledge Brokering Framework For Evaluation Unitsmentioning
confidence: 99%